Nativised Pprepositional verbs in Malaysian English from the perspective of language contact - Siew, Imm Tan (Pusat Pengajian Bahasa dan Linguistik, FSSK, UKM, 2013)
This study uses a corpus-based approach to explore processes of contact-induced change underlying the use of four nativised prepositional verbs (PrVs) in Malaysian English (ME)—comprise of, demand for, discuss about and discuss on. Located within Winford’s (2003) framework of group Second Language Acquisition (group SLA), this article compares the contexts of these PrVs with those of their corresponding single word verbs (SWVs). It is argued that there is a link between the polysemous nature of the SWVs comprise, demand and discuss in ME and the relevance of the nativised PrVs. Based on evidence of usage, it is concluded that the prepositions of, for, about and on in these PrVs are used to keep track of the transitivity of the SWVs in certain contexts. The fact that these PrVs recur in the relatively formal register of newspaper texts and the fact that they occur in systematic and stable syntactic environments suggest that they have become institutionalised. This study demonstrates the value of language contact theories—in particular, those within the group SLA framework—for elucidating the processes and outcomes of structural nativisation in varieties of English that have emerged in postcolonial settings.